ACTIVITY TEST OF Abrus precatorius L. LEAF EXTRACT AGAINST CLINICAL Streptococcus pneumonia GROWTH* - Misrahanum Misrahanum; Cut Intan Annisa Puteri; Cut Yulvizar (Jurnal Natural, 2017)
Abstract. Saga (Abrus precatorius L.) have been used by Indonesian community as a traditional medicine. The research aims to determine the activity of the methanol extract of saga leaves to inhibit the growth of clinical Streptococcus pneumoniae growth. Inhibition tests was done with casting cup method. The results showed that the methanol extract of saga leaves at a concentration of 37,5; 50; 62,5; 75 and 87,5 mg/mL formed growth inhibition zone of clinical S. pneumoniae with consecutive average of 0,5; 1,75; 2,82; 4,00; and 4,82 mm. Based on the results of the research can be concluded that the methanol extract of saga leaves had activity in inhibiting the growth of clinical S. pneumoniae isolates with low category.  Key words: Abrus precatorius L., Clinical Streptococcus pneumoniae, Methanol extract*Judul ini telah dipresentasikan pada Seminar Nasional: Indonesian Students Conference on Science and Mathematics(ISCSM) 11-12 November 2015, Banda Aceh Indonesia